Implementasi Digital Marketing pada UMKM “Cireng Mang Ade” di Bengkalis - Nopitasari, Fitri; Rizqa Arimurti; Rini Arvika Sari; Erma Domos (ABDIMAS TERAPAN : Jurnal Pengabdian Kepada Masyarakat Terapan, 2025)
This community service project aims to implement a digital marketing strategy for the "Cireng Mang Ade" SME in Bengkalis to expand market reach and increase product sales. The research method uses a descriptive qualitative approach with SWOT and STP analysis to identify the internal and external conditions of the business. The strategies applied include utilizing social media platforms Instagram and Facebook, creating a Google My Business account, and using the Maxim marketplace for promotion and delivery services. The results of the study show significant improvements in business visibility, social media follower growth, and consumer purchasing interest. Instagram reached 846 accounts with 81.8% new users, Facebook gained 546 active followers, Google My Business recorded 174 interactions, and Maxim facilitated easier product ordering and delivery. This digital marketing implementation has proven to be effective in expanding the market and increasing brand awareness as well as consumer engagement. The study demonstrates that the appropriate application of digital marketing can be an effective and sustainable solution for the development of SMEs in the digital era, helping them remain competitive and reach a wider consumer base.